Memanfaatkan Air Bilasan Bagas Untuk Menghasilkan Listrik Dengan Teknologi Microbial Fuel Cells - Suprapta Winaya, I Nyoman; Sucipta, Made; Krisna Wira Putra, A.A. (Jurnal Energi Dan Manufaktur; Vol 5, No.1 April 2011, 2012)
A microbial fuel cell design of fuel cells (MFC) by using the H type membrane (PEM) of the salt bridgeused in this study for the purpose of generating direct current electricity by making use of the rinse water Bagas.Bagas rinse water used to enrich microbes oxidizing the electron donor in the anode. Oxygen is pumped (forcedaeration) at the cathode. Within 7 to 9 days would be generated a steady flow system 240 mV. The use of moreelectrodes to extend electrode surface that is from 3, 6, and 9. And the use of two PEM has a thickness of 10 cmwith a different contact surface of each dianoda and cathode at 2 inches and 4 inches. So after testing is doneobtained data showing that the water blasan bagasse can be used to generate electricity with MFC technologyas well as with a combination of factors will also result in improved performance of the MFC.
Keywords: microbial fuel cell (MFC) type H, Proton Exchange Membrane (PEM) salt bridge, forced aeration, electrode, cathode, anode